Intelligent vibrotactile biofeedback system for real-time postural correction on perturbed surfaces - Gopalai, Alpha Agape; Senanayake, S.M.N.A.; Lim, Hann (IEEE, 2012)
Biofeedbacks delivery during rehabilitation have been known to improve postural control and shorten rehabilitation periods. A biofeedback system communicates with the human central nervous system (CNS) through a variety of feedback modalities. Among the many available modalities vibrotactile feedback devices are gaining much attention. This is due to their desirable characteristics and simplistic manner of presenting information to the CNS. An intelligent biofeedback system integrated with wireless sensors for monitoring postural control during rehabilitation was hypothesized to shorten rehabilitation periods. This work presents the design of a postural control measuring device integrated with real-time intelligent biofeedback for postural correction. The system integrates three modules: (a) inertial measurement units (IMUs), (b) fuzzy knowledge base, and (c) feedback driver circuit. Human posture is measured using Euler angular measurements from the IMUs. A fuzzy inference system (FIS) was used to determine quality of postural control, based on measurements from the IMUs. Forewarning of poor postural control is given by vibrotactile actuators (biofeedback). Experiments were conducted to test viability of the system in achieving accurate real-time measurements and interventions. The results observed improvements in postural control when biofeedback intervention was present.